Gender dynamics in seed systems - Pyburn, Rhiannon (CGIAR Collaborative Platform on Gender Research, 2017)
Presented by Rhiannon Pyburn (KIT), as part of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017